ANALISIS FAKTOR–FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG PASAR SENI SUKAWATI GIANYAR - aris artaman, dewa made; yuliarmi, ni nyoman; ketut, djayastra i (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 04.NO.02.TAHUN 2015, 2015)
Along with the development of globalization and competition in economy, the economic potential possessed by Sukawati Art Market as a prime tourism shopping spot for tourists gradually slows down, this is due to the development of modern souvenir markets selling similar handmade products as those offered in Sukawati Art Market. Other factors predicted to cause the declining of trend of traders’ revenue are internal factors such as venture capitals used that are mostly the equity capital, varies length of business and uncertain working hours. While external factors, namely, difference of strategic and non strategic business location and inadequate parking facilities are the other important factors affecting the traders’ income of Sukawati Art Market. The aims of this study are: 1) to analyze the effects of venture capital, length of business, working hours, parking and business locations simultaneously to traders’ income of Sukawati Art Market, 2) to analyze the effects of venture capital, length of business, working hours, parking and business location partially to traders’ income of Sukawati Art Market 3), to determine the dominant factors causing trend of traders’ income declining of Sukawati Art Market. The samples used were amounting of 89 respondents from traders of Sukawati Art Market. The results of simultaneous analysis showed that the variable venture capital, length of business, working hours, parking and business location significantly affect the traders’ income of Sukawati Art Market. For the result of partial analysis, the venture capital, length of business, and business location had positive effects on the traders’ income of Sukawati Art Market while variable of working hours and parking partially had negative effect to the traders’ revenue of Sukawati Art Market. Venture capital is the dominant variable affecting traders’ income; therefore, the variable of venture capital has an important role in the efforts to improve the income of traders. Traders expect loan or non collateral credit to improve their business.
Keywords: Income, Venture Capital, Length of Business, Working Hours, Parking and Business Location